Targeted next generation sequencing approach identifies eighteen new candidate genes in normosmic hypogonadotropic hypogonadism and Kallmann syndrome. (5th December 2016) - Quaynor, Samuel D.; Bosley, Maggie E.; Duckworth, Christina G.; Porter, Kelsey R.; Kim, Soo-Hyun; Kim, Hyung-Goo; Chorich, Lynn P.; Sullivan, Megan E.; Choi, Jeong-Hyeon; Cameron, Richard S.; Layman, Lawrence C.
Abstract: The genetic basis is unknown for ∼60% of normosmic hypogonadotropic hypogonadism (nHH)/Kallmann syndrome (KS). DNAs from (17 male and 31 female) nHH/KS patients were analyzed by targeted next generation sequencing (NGS) of 261 genes involved in hypothalamic, pituitary, and/or olfactory pathways, or suggested by chromosome rearrangements. Selected variants were subjected to Sanger DNA sequencing, the gold standard. The frequency of Sanger-confirmed variants was determined using the ExAC database. Variants were classified as likely pathogenic (frameshift, nonsense, and splice site) or predicted pathogenic (nonsynonymous missense). Two novel FGFR1 mutations were identified, as were 18 new candidate genes including: AMN1, CCKBR, CRY1, CXCR4, FGF13, GAP43, GLI3, JAG1, NOS1, MASTL, NOTCH1, NRP2, PALM2, PDE3A, PLEKHA5, RD3, and TRAPPC9, and TSPAN11 . Digenic and trigenic variants were found in 8/48 (16.7%) and 1/48 (2.1%) patients, respectively. NGS with confirmation by Sanger sequencing resulted in the identification of new causative FGFR1 gene mutations and suggested 18 new candidate genes in nHH/KS. Graphical abstract: Highlights: Targeted and Sanger DNA sequencing of 261 genes was performed in 48 patients with hypogonadotropic hypogonadism. Two novel FGFR1 likely pathogenic mutations were found. Nineteen new candidate genes for hypogonadotropic hypogonadism were identified. Eight possible digenic and one possible trigenic families were identified.